Worldviews and belief systems: a comparative introduction - Hashi, Abdurezak Abdulahi (Fajar Ulung, 2016)
Introduction, uses analytical and comparative methods, and intends to highlight the foundations and conceptions of dominant belief systems and philosophies of life. This book seeks to address the fundamental ideals and thoughts of given worldviews in a descriptive and comparative manner, however it does not intend to present a normative account, nor does it aim to produce any judgments of right and wrong. It explains the meaning and implications of the leading thoughts and ideals of given philosophies of life, and illustrates the differences and similarities among such belief systems. Apart from the introduction which highlights the rationale and the method used in this book, as well as the conclusion, which constitutes a summary of the ideas and thoughts presented in this work, this book includes seven chapters. The first chapter highlights basic concepts, understandings, functions and contents of the term “worldview”. The second chapter explains types of worldview, such as the scientific worldview, philosophical worldview and religious worldview, as well as ideologies and leading schools of thought. Foundations and concepts of conventional approaches to life such as materialism, modernism, positivism, secularism and postmodernism are highlighted in chapter three. Chapter four illustrates types and forms of religious belief systems and faiths such as polytheism, pantheism, monism, deism and monotheism. Theories and conceptions about religiosity, particularly the criterion of true religion, its functions in life, as well as scholastic debates about the evolution or origin of religious faiths are addressed in chapter five. Chapter six forms a concise exposition of the Islamic worldview, its scope and principles, with particular emphases on its definition, essential teachings and distinguishing attributes, while chapter seven presents a comparative overview of belief systems with regard to ontology, theology, the origin of life, eschatology, epistemology, axiology, and anthropology. The central idea of this work is to offer, for the beginners in this field, an opportunity to read about different perspectives on these subjects. With this comparative account of the foundations and attributes of worldviews, the writer hopes that this book will serve as an introduction to the philosophies of life for beginners, new students and learners in this important and challenging field. Because the book aims to introduce the subjects of this field to beginners and new learners, the writer emphasizes technical and conceptual definitions as well as the philosophical implications of given concepts and thoughts. In addition, it is true that the study of belief systems and fundamental commitments of life of given societies and communities is very sensitive and sometimes a delicate task, but given the fact that today we are living in a globalized village, whereby no man is an island, and in which people of different faiths and beliefs are rubbing shoulders in all levels of life, today we have no choice but to study worldviews and belief systems, the foundations of cultures and traditions, so that our understanding of each other is improved and enriched, and the potential and real tensions among communities are eased. It is this effort, the desire to form mutual understanding and contribute to peaceful co-existence among global societies, which this book seeks to serve. Hence the subjects and discussions of this book are written to assist those who wish to read and understand the spirit and foundations of belief systems and worldviews in a comparative manner.